1996
DOI: 10.1364/ol.21.000767
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear spatial filtering with a dye-doped liquid-crystal cell

Abstract: Light-induced molecule reorientation in dye-doped liquid crystals has been applied to nonlinear spatial filtering of periodic patterns. Photoisomerization of azo-dye molecules leads to local alignment changes in the liquidcrystal molecules because of interaction among the molecules. Consequently the polarization of transmitted light is modulated, depending on the induced light intensity. By selection of suitable polarization of the transmitted light self-aligned filtering is realized. Both temporal response an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…The defects are enhanced, but their vicinity is not free of other structures. This can be veri®ed by numerical simulations, when a complex object consisting of rectangular, circular and grating-like structures is examined (see section 6).…”
Section: Self-®ltering Procedures With Optically Addressed Spatial Ligmentioning
confidence: 84%
See 1 more Smart Citation
“…The defects are enhanced, but their vicinity is not free of other structures. This can be veri®ed by numerical simulations, when a complex object consisting of rectangular, circular and grating-like structures is examined (see section 6).…”
Section: Self-®ltering Procedures With Optically Addressed Spatial Ligmentioning
confidence: 84%
“…The ®ltering element is positioned in the second Fourier plane, FP 2 (see ®gure 6). Most experiments depicted below have been performed with ¶ = 633 nm and a 40 £ /0.65 microscope objective.…”
Section: Self-®ltering Procedures With Bso: Experimental Resultsmentioning
confidence: 99%
“…While our group demonstrated a self-adaptive all-optical Fourier image processing system using photoinduced dichroic characteristics [22], Korchemskaya's group exploited photoinduced anisotropy for real-time selective image processing [23]. On the other hand, several other groups exploited similar photoinduced polarization rotation properties of azobenzene dye doped liquid crystal and polymer films for spatial filtering [24][25][26]. Simply by placing a polarizer sheet at the Fourier plane, Ferrari et al demonstrated phase visualization and edge enhancement [27].…”
Section: Photoinduced Anisotropy For Medical Image Processingmentioning
confidence: 99%
“…Such a configuration extends over at least two focal lengths of both lenses and is of a relatively large size -it could hardly be used in micro-or nano-scale photonic devices. Other, more sophisticated arrangements for spatial filtering based on liquid-crystal cells [2], utilization of thin film interfaces [3], anisotropic media [4], metallic grids [5], possibly including monolithically integrated passive beam shaping elements [6], etc. have not resulted in widespread technological applications.…”
Section: Introductionmentioning
confidence: 99%